Can bone marrow cellularity help in predicting prognosis in myelodysplastic syndromes?. (31st August 2018) - Greenbaum, Uri; Joffe, Erel; Filanovsky, Kalman; Oster, Howard S.; Kirgner, Ilya; Levi, Itai; Raanani, Pia; Avivi, Irit; Manor, Esther; Man‐El, Gili; Mittelman, Moshe
Abstract: Objectives: To ascertain the relevance of bone marrow cellularity (BMC) to the interpretation of blast percentage (blast%) in MDS prognostication. Methods: We compared survival prediction based on blast% adjusted to different levels of cellularity, compared to the survival based on the original IPSS‐R blast% grouping. Results: We analyzed 355 consecutive MDS patients. Cellularity, in and of itself or its interaction with blast%, was not associated with overall survival (OS). In a small subset of patients with a hypercellular marrow (15%; n = 26), dismal prognosis was observed at lower levels of blast%. For these cases OS was similar to higher IPSS‐R blast groups. For example, within the Intermediate group (blast% 5%‐10%), those with a hypercellular marrow and >6% blasts had an OS of 10 m similar to 16 m in the High (blast% 10%‐19%) blast group. These changes did not translate into a significant improvement in overall prognostic power of a cellularity‐adjusted IPSS‐R (C index 0.71 vs. 0.70). Conclusion: Adjusting blast% to cellularity did not improve prognostication. However, within IPSS‐R‐defined blast groups, a small subset of patients with relatively higher blast% and hypercellularity may have a worse prognosis than expected.